Exploratory Study of TARGET Model of Motivation - Muhammad Saeed, Marina Ilyas (JCTE, 2023)
The study is designed to explore the use of TARGET model of motivation in university classrooms. This case study also explores, whether the practices of model were used to create mastery climate or ego climate. The sample of the study was comprised of 20 students of B.Ed. (Hons.) program from University of Education Lahore, Pakistan. Participants were selected by using purposive sampling technique. Semistructured interview schedule was used for the data collection. Data were transcribed and coded into interpretive categories according to the research objectives and questions. Thematic inductive approach was used for analyzing the data. Major findings of this study revealed that teachers were practicing TARGET model as an instructional strategy in university classrooms, although unintentionally in mastery dimension. In a masteryoriented environment, the focus of students in class was on learning rather than to competition.